Prevalence and Seasonal Pattern of Anal Fissure in Rural Hospital of Nepal (Journal of KIST Medical College, 2020)
Introduction: Anal Fissure (AF) is a longitudinal tear in the epithelium of the anoderm within the anal canal. It is associated with symptoms of severe anal pain and rectal bleeding. While searching for literatures on AF prevalence in Nepal, there were hardly any systematic published studies except a few studies that mostly focused in the treatment and outcome of the disease. The objective of the present study is to report on AF prevalence with its seasonal pattern among anorectal disorder patients from this rural part of Nepal.Methods: This was a retrospective cross-sectional study from June 2015 to March 2020 at the Karnali Academy of Health Sciences. The demographic characteristics features of anal fissure were recorded. Cases included all hemorrhoids, perianal abscess and fistula in Ano with a bleeding history. Previous fistulectomy, biopsy-proven tuberculosis and malignancy were excluded. Statistical analysis was performed using SPSS 16.Results: A total of 1768 patients with ano-rectal disorders visited surgical outpatient department OPD) during the study period. Of 1768 patients, 415 patients (23.47%) had anal fissures. The mean age of patients was 29.02±13.58 years. There were 176 male patients (42.4%) and 239 (57.6%) patients were female. The majority (n=148; 35.7%) of patients were in the group 20 to 29 years. Most of the patients with anal fissure visited during winter time (42.7%).Conclusion: Anal fissure is common anorectal problem, with slight female predominance. The majority was found to affect the adolescent group